2013
DOI: 10.1152/ajpendo.00596.2012
|View full text |Cite
|
Sign up to set email alerts
|

FGF23 is a novel regulator of intracellular calcium and cardiac contractility in addition to cardiac hypertrophy

Abstract: Recent observational studies in humans suggest that circulating FGF23 is independently associated with cardiac hypertrophy and increased mortality, but it is unknown whether FGF23 can directly alter cardiac function. We found that FGF23 significantly increased cardiomyocyte cell size in vitro, the expression of gene markers of cardiac hypertrophy, and total protein content of cardiac muscle. In addition, FGFR1 and FGFR3 mRNA were the most abundantly expressed FGF receptors in cardiomyocytes, and the coreceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
158
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(176 citation statements)
references
References 56 publications
15
158
2
1
Order By: Relevance
“…44 In cultured cardiomyocytes, FGF23 can induce a rise in intracellular calcium that can be prevented by pretreatment with verapamil. 45 Both PTH and FGF23 progressively rise with loss of kidney function in humans with CKD 46 and this animal model, perhaps explaining the increased calcium influx, and might further alter normal calcium recycling within the cytoplasm. This result, together with a downregulation of SERCA2a, may lead to a concomitant increase in arrhythmias.…”
Section: Discussionmentioning
confidence: 84%
“…44 In cultured cardiomyocytes, FGF23 can induce a rise in intracellular calcium that can be prevented by pretreatment with verapamil. 45 Both PTH and FGF23 progressively rise with loss of kidney function in humans with CKD 46 and this animal model, perhaps explaining the increased calcium influx, and might further alter normal calcium recycling within the cytoplasm. This result, together with a downregulation of SERCA2a, may lead to a concomitant increase in arrhythmias.…”
Section: Discussionmentioning
confidence: 84%
“…Hence, of great relevance to these epidemiologic observations were the landmark findings of Faul et al (7), showing that FGF23 can directly induce hypertrophic gene programs in the cardiomyocyte, leading to LVH at the elevated levels seen in some advanced CKD patients. Independent investigators have subsequently corroborated these finding, showing the hypertrophic effect of FGF23 on cultured cardiomyocytes, and suggested that FGF23 might also have additional effects on myocardial contractility (68). Notably, in the study by Faul et al (7), these effects were apparently transduced by the FGF receptor independent of a-klotho, which, according to the current paradigm, is an obligate coreceptor for physiologic FGF23 signaling in the kidney tubules and parathyroid glands (69).…”
Section: Fgf23-direct Link To Pathology?mentioning
confidence: 92%
“…Recently, Faul et al (16) and our research group (67) have shown that high concentrations of FGF23 have direct actions on the heart that alter contractile performance and induce cardiac hypertrophy. These data strongly suggest that FGF23 has the potential to directly initiate some of the pathological cardiovascular changes observed during CKD.…”
mentioning
confidence: 98%